HUBUNGAN MINAT MEMBACA DENGAN KETERAMPILAN MENULIS PUISI PADA SISWA KELAS IV SDN 85 SINGKAWANG - Nur Romadhani; Gunta Wirawan; Safrihady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between reading interest and poetry writing skills among fourth-grade students at SDN 85 Singkawang. This research employed a quantitative approach with a correlational method. The subjects of the study consisted of 20 fourth-grade students. The instruments used were a questionnaire to measure reading interest and a poetry writing test to assess students’ poetry writing skills. The collected data were analyzed using the Pearson Product Moment correlation. The results showed a positive and significant relationship between students’ reading interest and their poetry writing skills. The higher the students’ interest in reading, the better their ability to write poetry. These findings highlight the importance of fostering a reading literacy culture in elementary school settings to support students' creative writing skills.